Peningkatan Minat Belajar Peserta Didik Pada Pembelajaran PAI Melalui Asesmen Diagnostik Non-Kognitif - Maria, Anly; Shiam, Siti Nurpajri (STAI Al-Musaddadiyah Garut, 2024)
This research examines increasing students' interest in learning PAI through non-cognitive diagnostic assessments in Phase B SDIT Al-Furqon Garut. Interest is a process that gives enthusiasm, direction and persistence of behavior. This means that motivated behavior is behavior that is full of energy, directed and long-lasting. In learning activities, motivation can be said to be the overall driving force within students which gives rise to learning activities, which ensures the continuity of learning activities and provides direction to learning activities, so that the goals desired by the learning subject can be achieved. However, in reality, students' interest in learning in Phase B SDIT Al-Furqon Garut is still low, this is proven by the results of pre-research observations. About 34% of the 26 students showed that they already had an interest in learning, so stimulus was needed, one of which was carrying out a non-cognitive diagnostic assessment before carrying out learning activities. The aim of this research is to describe the significance of using non-cognitive diagnostic assessments to increase students' learning interest in PAI learning in Phase B SDIT Al-Furqon Garut. The method used in this research is the Classroom Action Research (PTK) method. Data collection techniques include observation, questionnaires, interviews and documentation. The data analysis technique in PTK only uses simple statistical formulas to find the average value and percentage of learning completeness. Based on the results of classroom action research carried out in two cycles, there was an increase in students' interest in learning in cycle I to 45%, then experienced another increase in cycle II to 80%. It can be understood that there is a significant increase in students' learning demands of 22% from pre-cycle to cycle I and 30% from cycle I to cycle II. So overall there is an increase in students' interest in learning with a significance of 50% from pre-cycle to cycle II. Keywords: Islamic Religious Education, Interest in Learning, Non-Cognitive Diagnostic Assesment